Aerosol Transmission of SARS-CoV-2: Inhalation as well as Exhalation Matters for COVID-19 Reply - Echternach, Matthias; Westphalen, Caroline; Koeberlein, Marie Christine; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2021)
CRIS-Team WoS Importer:2021-05-21

Effect of functional electric stimulation on phonation in an ex vivo aged ovine model - Jakubaß, Bernhard; Peters, Gregor; Kniesburges, Stefan; Semmler, Marion; Kirsch, Andrijana; Gerstenberger, Claus; Gugatschka, Markus; Döllinger, Michael (Journal of the Acoustical Society of America, 2023)
With age, the atrophy of the thyroarytenoid muscle (TAM), and thus atrophy of the vocal folds, leads to decreased glottal closure, increased breathiness, and a loss in voice quality, which results in a reduced quality of life. A method to counteract the atrophy of the TAM is to induce hypertrophy in the muscle by functional electric stimulation (FES). In this study, phonation experiments were performed with ex vivo larynges of six stimulated and six unstimulated ten-year-old sheep to investigate the impact of FES on phonation. Electrodes were implanted bilaterally near the cricothyroid joint. FES treatment was provided for nine weeks before harvesting. The multimodal measurement setup simultaneously recorded high-speed video of the vocal fold oscillation, the supraglottal acoustic signal, and the subglottal pressure signal. Results of 683 measurements show a 65.6% lower glottal gap index, a 22.7% higher tissue flexibility (measured by the amplitude to length ratio), and a 473.7% higher coefficient of determination (R2) of the regression of subglottal and supraglottal cepstral peak prominence during phonation for the stimulated group. These results suggest that FES improves the phonatory process for aged larynges or presbyphonia.
CRIS-Team Scopus Importer:2023-05-19

Effects of surgical masks on aerosol dispersion in professional singing - Kniesburges, Stefan; Schlegel, Patrick; Peters, Gregor; Westphalen, Caroline; Jakubaß, Bernhard; Veltrup, Reinhard; Kist, Andreas; Döllinger, Michael; Gantner, Sophia; Kuranova, Liudmila; Benthaus, Tobias; Semmler, Marion; et al. (Journal of Exposure Science and Environmental Epidemiology, 2021)
Background In the CoVID-19 pandemic, singing came into focus as a high-risk activity for the infection with airborne viruses and was therefore forbidden by many governmental administrations. Objective The aim of this study is to investigate the effectiveness of surgical masks regarding the spatial and temporal dispersion of aerosol and droplets during professional singing. Methods Ten professional singers performed a passage of the Ludwig van Beethoven's "Ode of Joy" in two experimental setups-each with and without surgical masks. First, they sang with previously inhaled vapor of e-cigarettes. The emitted cloud was recorded by three cameras to measure its dispersion dynamics. Secondly, the naturally expelled larger droplets were illuminated by a laser light sheet and recorded by a high-speed camera. Results The exhaled vapor aerosols were decelerated and deflected by the mask and stayed in the singer's near-field around and above their heads. In contrast, without mask, the aerosols spread widely reaching distances up to 1.3 m. The larger droplets were reduced by up to 86% with a surgical mask worn. Significance The study shows that surgical masks display an effective tool to reduce the range of aerosol dispersion during singing. In combination with an appropriate aeration strategy for aerosol removal, choir singers could be positioned in a more compact assembly without contaminating neighboring singers all singers.
CRIS-Team WoS Importer:2021-10-15

Einfluss der Stimmlippenoberfläche und asymmetrischer Elastizitätsmodule auf die Phonation - Peters, Gregor; Lodermeyer, Alexander; Kutz, Anne; Gröhn, Franziska; Becker, Stefan (Fortschritte der Akustik – DAGA 2017 (Kiel, 03/06/17 - 03/09/17), 2017)

Extent and Effect of Covering Laryngeal Structures with Synthetic Laryngeal Mucus via Two Different Administration Techniques - Semmler, Marion; Lasar, Sarina; Kremer, Franziska; Reinwald, Laura; Wittig, Fiori; Peters, Gregor; Schraut, Tobias; Wendler, Olaf; Seyferth, Stefan; Schützenberger, Anne; Dürr, Stephan (Journal of Voice, 2023)
Objective: The first goal of this study was to investigate the coverage of laryngeal structures using two potential administration techniques for synthetic mucus: inhalation and lozenge ingestion. As a second research question, the study investigated the potential effects of these techniques on standardized voice assessment parameters. Methods: Fluorescein was added to throat lozenges and to an inhalation solution to visualize the coverage of laryngeal structures through blue light imaging. The study included 70 vocally healthy subjects. Fifty subjects underwent administration via lozenge ingestion and 20 subjects performed the inhalation process. For the first research question, the recordings from the blue light imaging system were categorized to compare the extent of coverage on individual laryngeal structures objectively. Secondly, a standardized voice evaluation protocol was performed before and after each administration to determine any measurable effects of typical voice parameters. Results: The administration via inhalation demonstrated complete coverage of all laryngeal structures, including the vocal folds, ventricular folds, and arytenoid cartilages, as visualized by the fluorescent dye. In contrast, the application of the lozenge predominantly covered the pharynx and laryngeal surface toward the aryepiglottic fold, but not the inferior structures. All in all, the comparison before and after administration showed no clear effect, although a minor deterioration of the acoustic signal was noted in the shimmer and cepstral peak prominence after the inhalation. Conclusions: Our findings indicate that the inhalation process is a more effective technique for covering deeper laryngeal structures such as the vocal folds and ventricular folds with synthetic mucus. This knowledge enables further in vivo studies on the role of laryngeal mucus in phonation in general, and how it can be substituted or supplemented for patients with reduced glandular activity as well as for heavy voice users.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Blue light imaging; Fluorescein; High-speed videoendoscopy; Inhalation; Lozenge; Synthetic mucus

Human laryngeal mucus from the vocal folds: Rheological characterization by particle tracking microrheology and oscillatory shear rheology - Peters, Gregor; Wendler, Olaf; Böhringer, David; Gostian, Antoniu Oreste; Müller, Susanna; Canziani, Herbert; Hesse, Nicolas; Semmler, Marion; Berry, David A.; Kniesburges, Stefan; Peukert, Wolfgang; Döllinger, Michael (Applied Sciences, 2021)
Mucus consistency affects voice physiology and is connected to voice disorders. Neverthe-less, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementary approaches: 19 samples were successfully applied to particle tracking microrheology (PTM) and five additional samples to oscillatory shear rheology (OSR). Mucus was collected by experienced laryngologists from patients together with demographic data. The analysis of the viscoelasticity revealed diversity among the investigated mucus samples according to their rigidity (absolute G’ and G”). Moreover some samples revealed throughout solid-like character (G’ > G”), whereas some underwent a change from solid-like to liquid-like (G’ < G”). This led to a subdivision into three groups. We assume that the reason for the differences is a variation in the hydration level of the mucus, which affects the mucin concentration and network formation factors of the mucin mesh. The demographic data could not be correlated to the differences, except for the smoking behavior. Mucus of predominant liquid-like character was associated with current smokers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Human laryngeal mucus; Oscillatory shear rheology; Particle tracking microrheology; Viscoelasticity; Vocal folds

Impulse dispersion of aerosols during playing the recorder and evaluation of safety measures - Köberlein, Marie; Hermann, Laila; Gantner, Sophia; Tur, Bogac; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Döllinger, Michael; Kniesburges, Stefan; Echternach, Matthias (PLoS ONE, 2022)
INTRODUCTION: Group musical activities using wind instruments have been restricted during the CoVID19 pandemic due to suspected higher risk of virus transmission. It was presumed that the aerosols exhaled through the tubes while playing would be ejected over larger distances and spread into the room due to jet stream effects. In particular, the soprano recorder is widely used as an instrument in school classes, for beginners of all age groups in their musical education, in the context of leisure activities and in professional concert performances. Understanding the aerosol impulse dispersion characteristics of playing the soprano recorder could assist with the establishment of concepts for safe music-making. METHODS: Five adult professionally trained soprano recorder players (4 female, 1 male) played four bars of the main theme of L. van Beethoven's "Ode to Joy" in low and in high octaves, as well as with 3 different potential protection devices in the high octave. For comparison they spoke the corresponding text by F. Schiller. Before each task, they inhaled .5 L of vapor from an e-cigarette filled with base liquid. The vapor cloud escaping during speaking or playing was recorded by cameras and its spread was measured as a function of time in the three spatial dimensions. The potential safety devices were rated for practicability with a questionnaire, and their influence on the sound was compared, generating a long-term average spectrum from the audio data. RESULTS: When playing in the high octave, at the end of the task the clouds showed a median distance of 1.06 m to the front and .57 m diameter laterally (maxima: x: 1.35 m and y: .97 m). It was found that the clouds' expansion values in playing the recorder with and without safety measures are mostly lower when compared to the ordinary, raised speaking voice of the same subjects. The safety devices which covered the instrument did not show clear advantages and were rated as unpractical by the subjects. The most effective reduction of the cloud was reached when playing into a suction funnel. CONCLUSION: The aerosol dispersion characteristics of soprano recorders seem comparable to clarinets. The tested safety devices which covered holes of the instrument did not show clear benefits.
CRIS-Team Scopus Importer:2022-10-07

Impulse dispersion of aerosols during playing wind instruments - Gantner, Sophia; Echternach, Matthias; Veltrup, Reinhard; Westphalen, Caroline; Köberlein, Marie Christine; Kuranova, Liudmila; Peters, Gregor; Jakubaß, Bernhard; Benthaus, Tobias; Döllinger, Michael; Kniesburges, Stefan (PLoS ONE, 2022)
Musical activities, especially singing and playing wind instruments, have been singled out as potentially high-risk activities for the transmission of SARS CoV-2, due to a higher rate of aerosol production and emission. Playing wind instruments can produce condensation, droplets of saliva, and aerosol particles, which hover and spread in the environmental air's convectional flows and which can be potentially infectious. The aim of this study is to investigate the primary impulse dispersion of aerosols that takes place during the playing of different wind instruments as compared to breathing and to speaking. Nine professional musicians (3 trumpeters, 3 flautists and 3 clarinetists) from the Bavarian Symphony Orchestra performed the main theme from the 4th movement of Ludwig van Beethoven's 9th symphony in different pitches and loudness. The inhaled air volume was marked with small aerosol particles produced using a commercial e-cigarette. The expelled aerosol cloud was recorded by cameras from different perspectives. Afterwards, the dimensions and dynamics of the aerosol cloud were measured by segmenting the video footage at every time point. Overall, the flutes produced the largest dispersion at the end of the task, reaching maximum forward distances of 1.88 m. An expulsion of aerosol was observed in different directions: Upwards and downwards at the mouthpiece, at the end of the instrument, and along the flute at the key plane. In comparison, the maximum impulse dispersions generated by the trumpets and clarinets were lower in frontal and lateral direction (1.2 m and 1.0 m towards the front, respectively). Also, the expulsion to the sides was lower.
CRIS-Team Scopus Importer:2022-03-11

Impulse Dispersion of Aerosols during Singing and Speaking: A Potential COVID-19 Transmission Pathway - Echternach, Matthias; Gantner, Sophia; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2020)
CRIS-Team Scopus Importer:2020-12-11

Reply to Philip et al. - Echternach, Matthias; Westphalen, Caroline; Koeberlein, Marie Christine; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (American Journal of Respiratory and Critical Care Medicine, 2021)
CRIS-Team Scopus Importer:2021-05-21

Sources of Aerosol Dispersion During Singing and Potential Safety Procedures for Singers - Westphalen, Caroline; Kniesburges, Stefan; Veltrup, Reinhard; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Köberlein, Marie; Döllinger, Michael; Echternach, Matthias (Journal of Voice, 2021)
Introduction: With respect to the Covid-19 pandemic, singing is assumed to be associated with a high potential person-to-person transmission. However, it remains unclear how the impulse dispersion varies with different types of articulation, intensity levels of diction, or body position. Furthermore, it has not been understood in detail how to prevent aerosol dispersion during singing. Material and Methods: Single professional singers from the Bavarian Radio Chorus were asked to sing in different head positions, with different articulation patterns and different masks after inhaling the basic liquid of an e-cigarette. The vapor cloud was segmented and tracked over time. Results: Consonants and exaggeration of diction enhanced the distance reached by the impulse dispersion. Furthermore, the greatest dispersion was reached for a neutral head position. All protection masks stopped the initial jet of the aerosols but the FFP2 masks were the most effective. Conclusion: Some protection equipment has been identified to be promising in reducing aerosol dispersion. However, systematic effects have to be evaluated in greater collectives.
CRIS-Team Scopus Importer:2021-04-19
Keywords: SingErs—AeroSols—COVID-19

Synthetic mucus for an ex vivo phonation setup: Creation, application, and effect on excised porcine larynges - Peters, Gregor; Jakubaß, Bernhard; Weidenfeller, Katrin; Kniesburges, Stefan; Böhringer, David; Wendler, Olaf; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Berry, David A.; Döllinger, Michael; Semmler, Marion (Journal of the Acoustical Society of America, 2022)
Laryngeal mucus hydrates and lubricates the deformable tissue of the vocal folds and acts as a boundary layer with the airflow from the lungs. However, the effects of the mucus' viscoelasticity on phonation remain widely unknown and mucus has not yet been established in experimental procedures of voice research. In this study, four synthetic mucus samples were created on the basis of xanthan with focus on physiological frequency-dependent viscoelastic properties, which cover viscosities and elasticities over 2 orders of magnitude. An established ex vivo experimental setup was expanded by a reproducible and controllable application method of synthetic mucus. The application method and the suitability of the synthetic mucus samples were successfully verified by fluorescence evidence on the vocal folds even after oscillation experiments. Subsequently, the impact of mucus viscoelasticity on the oscillatory dynamics of the vocal folds, the subglottal pressure, and acoustic signal was investigated with 24 porcine larynges (2304 datasets). Despite the large differences of viscoelasticity, the phonatory characteristics remained stable with only minor statistically significant differences. Overall, this study increased the level of realism in the experimental setup for replication of the phonatory process enabling further research on pathological mucus and exploration of therapeutic options. (c) 2022 Acoustical Society of America.
CRIS-Team WoS Importer:2023-01-06

The Effect of Singers’ Masks on the Impulse Dispersion of Aerosols During Singing - Echternach, Matthias; Herrmann, Laila; Gantner, Sophia; Tur, Bogac; Peters, Gregor; Westphalen, Caroline; Benthaus, Tobias; Köberlein, Marie; Kuranova, Liudmila; Döllinger, Michael; Kniesburges, Stefan (Journal of Voice, 2021)
Background: During the Covid-19 pandemic, singing activities were restricted due to several super-spreading events that have been observed during rehearsals and vocal performances. However, it has not been clarified how the aerosol dispersion, which has been assumed to be the leading transmission factor, could be reduced by masks which are specially designed for singers. Material and Methods: Twelve professional singers (10 of the Bavarian Radio-Chorus and two freelancers, seven females and five males) were asked to sing the melody of the ode of joy of Beethoven's 9th symphony “Freude schöner Götterfunken, Tochter aus Elisium” in D-major without masks and afterwards with five different singers’ masks, all distinctive in their material and proportions. Every task was conducted after inhaling the basic liquid from an e-cigarette. The aerosol dispersion was recorded by three high-definition video cameras during and after the task. The cloud was segmented and the dispersion was analyzed for all three spatial dimensions. Further, the subjects were asked to rate the practicability of wearing the tested masks during singing activities using a questionnaire. Results: Concerning the median distances of dispersion, all masks were able to decrease the impulse dispersion of the aerosols to the front. In contrast, the dispersion to the sides and to the top was increased. The evaluation revealed that most of the subjects would reject performing a concert with any of the masks. Conclusion: Although, the results exhibit that the tested masks could be able to reduce the radius of aerosol expulsion for virus-laden aerosol particles, there are more improvements necessary to enable the practical implementations for professional singing.
CRIS-Team Scopus Importer:2021-10-15
Keywords: Aerosols; COVID19; Dispersion; Singing